Identification of Damping Characteristics of EPDM-RUBBER with applications to sandwiched beams and considerations to Engine Mounts for Performance Evaluation. (2020) - Prasad, V.B.S.Rajendra; Dr.G.VenkataRao,; Idrees, Mohammed
Abstract: Vibrations are undesirable in many fields owing to its adverse effects therefore as a control procedure, methods have been developed to prevent these vibrations. One of the methods is using dampers. Rubbers are widely used for damping the vibrations of various structures because of its low elastic modulus and high bulk modulus. Behavior of rubber can be classified as Hyper-elastic and Visco-elastic. In FEA rubbers or more precisely elastomers are modeled as Hyper-elastic. Hyper-elastic is a type of constitutive model for rubber like materials and provides a means of specifying their behavior which cannot be exactly specified by linear elastic models. In view of this an attempt is made to identify the damping characteristics of EPDM-RUBBER-rubber, which were identified by using sandwiched structures. Then the engine mount was modeled using this EPDM-RUBBER-rubber as a Hyper-elastic rubber, using the best fit Hyper-elastic material model, and then the performance of selected engine mounts with EPDM-RUBBER as their core rubber was studied for static, harmonic and time varying loads.